Mortality from cancer and other causes in the Balangero cohort of chrysotile asbestos miners. Issue 12 (29th July 2009) - Pira, E; Pelucchi, C; Piolatto, P G; Negri, E; Bilei, T; La Vecchia, C
Abstract : Objectives: To provide further information on mortality from cancer and other causes among chrysotile asbestos miners several years after exposure ceased, we updated the analyses from the Balangero mine worker cohort with follow-up to the end of 2003. Methods: The cohort included 1056 men, for a total of 34 432 man-years of observation. We obtained employment data from factory personnel records, and ascertained vital status and causes of death through population registers and death certificates from municipal registration offices. We computed expected numbers of deaths and standardised mortality ratios (SMRs) for relevant causes using the province of Turin and national death rates, for each 5-year calendar period and age group. Results: We found a significant excess mortality from pleural cancer only (4 deaths, SMR 4.67) and pleural and peritoneal cancers combined (5 deaths, SMR 3.16). All pleural and peritoneal cancer deaths occurred 30 or more years after first exposure. The SMRs were 1.27 for lung cancer (45 deaths), 1.82 for laryngeal cancer (8 deaths) and 1.12 for all cancers (142 deaths). Cumulative dust exposure and the various time factors considered did not show a clear pattern of risk associated with mortality from lung cancer. There were 57 deaths from cirrhosis (SMR 2.94) and 54 from accidents and violence (SMR 1.88). Overall, we observed a total of 590 deaths as compared to 412.9 expected (SMR 1.43). Conclusions: This updated analysis, with almost 60% of the cohort having died, confirmed the excess mortality from pleural and peritoneal cancers and from several alcohol-related causes.